Microfluidic lung-on-a-chip for assessment of naonotoxicity - Tan, Fei Yang (Nanyang Technological University, 2021)
Organs-on-a-chip are miniaturized tissues and organs grown in vitro that enable modelling of human physiology and disease. For effective phenotypic screening, it is critical that the assay captures various aspects of complex human physiology. For this FYP, a novel 3D lung-on-a-chip model was developed to exhibit in vivo lung-like tissue structure and function. The proposed configuration facilitates crosstalk between the Human Lung Fibroblast, Human Umbilical Vein Endothelial Cells Green Fluorescent Protein and the A549 epithelial cells while minimizing direct cell-cell interactions due to rapid fibroblast proliferation.